The effect of arginine on the Wnt/β-catenin signaling pathway during porcine intramuscular preadipocyte differentiation. Issue 1 (9th January 2017) - Chen, Xiaoling; Luo, Yanliu; Jia, Gang; Liu, Guangmang; Zhao, Hua; Huang, Zhiqing
Abstract : Dietaryl -arginine supplementation decreases backfat thickness and increases intramuscular fat content in growing-finishing pigs, but the underlying mechanisms are unknown. Abstract : Dietaryl -arginine supplementation decreases backfat thickness and increases intramuscular fat content in growing-finishing pigs, but the underlying mechanisms are unknown. In this study, the effect of arginine on differentiation of porcine intramuscular preadipocytes was investigated in vitro . We showed that the mRNA and protein expressions of the peroxisome proliferator-activated receptor γ (PPARγ) and CCAAT/enhancer binding protein α were upregulated by arginine supplementation. Furthermore, the intracellular triglyceride level was increased by arginine supplementation. We also showed that activation of the Wnt/β-catenin signal pathway by using lithium chloride (LiCl) significantly attenuated arginine-induced upregulation of PPARγ and increased the phospho-β-catenin level. These findings suggested that arginine promotes porcine intramuscular preadipocyte differentiation, which might be via repressing the Wnt/β-catenin signaling pathway.